Pengaruh Direct Instruction Model Terhadap Keterampilan Bermain Kegiatan EKstrakurikuler Futsal Siswa Menengah Kejuruan - Muhammad Rhico Syandhiva; Ega Trisna Rahayu; Siswanto Siswanto (Peneliti.net, 2022)
This study aims to analyze and test the correctness of hypotheses regarding the Influence of Direct Instruction Model on the Play Skills of Vocational Secondary Students. This research was conducted at SMK Karya Guna Bhakti 2 Bekasi City. This research was conducted using quantitative approaches and experimental methods. The population in this study was all students who took part in the extracurricular futsal with a sampling technique, namely purposive sampling, then the sample size used was 30 students. The instrument used through observation refers to the GPAI. The analysis tool used is SPSS software with paired t-test. The results of this study explained that there were significant results seen through different average values, namely pretests of 11.97 and after being given treatment and posttesting the average value rose to 28.70. That is, the implementation of the direct instruction model affects students' playing skills in extracurricular futsal, as seen in the change in the average score before and after being given treatment. Also supported by the results of standard deviation and standard error obtained Thitung (-28.129) < Ttabel (2.042). The results of this hypothesis show that there is a significant influence between direct instruction models on students' play skills after treatment.